An Independent Damped Algorithm Based on SINS for Ship - Bo, Xu; Feng, Sun (2009 International Conference on Computer Engineering and Technology, 2009)
A novel damped compensation algorithm was presented in the paper. According to the control theory, the system add three different damp feedback in three loops, which is made use of its own velocity information to do compensation of errors. As the velocity compensation will make the system more sensitive, so the design of the parameters is very important. This paper gives the parameters according to the characteristics of the movement of the ships. Simulations and experimental results show that the inner automation algorithm can damp most of the Schuler and Foucault oscillations, and so efficiently improves the precision of the SINS on ships.